Frequency characteristics of slot-less and slot type linear oscillatory actuator for food processing application - Raja Othman, Raja Nor Firdaus Kashfi; Abdul Shukor, Fairul Azhar; Sulaiman, Farina; Mat Isa, Siti Zulaika; Vaithilingam, Aravind Chockalingam; Norhisam, Misron (Taylor's University, 2019)
This paper discusses RL frequency characteristics of slot-less and slot-type linear oscillatory actuator for food processing application. The RL characteristics experiment is carried out to investigate the characteristics of resistance and inductance for various value of frequency. The main objective of this research is to study the relationship of frequency response toward RL characteristics. The reason for this investigation is due to the controllable DC rectifier that will provide DC in pulse width modulation (PWM) signal to obtain the variable value of DC in average. The value of resistance and inductance is different when the shaft moves at a certain position. Physically, the slot-type linear motor was mounted on the linear jig and the shaft has been fully pulled out. The value of the resistance and inductance was measured by using a LCR meter. In conclusion, this paper provides an overview of RL characteristics of slot-less and slot-type linear motor